The current situation and factors influencing the use of traditional Chinese medicine therapies among patients with chronic disease in china: a cross-sectional study - Yifei Cao; Ting Huang; Haoyan Deng; Jingyi Zhang; Fengjiao Guo; Wenqiang Yin; Jinwei Hu; Zhongming Chen; Hongwei Guo (Scientific Reports)
Abstract Chronic noncommunicable diseases, which can be referred to as chronic diseases, have become a significant challenge to global public health. Various studies have shown that traditional Chinese medicine (TCM) therapies are effective means of preventing and treating chronic diseases. The purpose of our study was to analyze the present circumstances of the use of TCM therapies among Chinese patients who have chronic diseases and explore the related influencing factors. Using datasets from the 2021 China General Social Survey (CGSS), we collected basic information, health status, and lifestyle data from 1,023 residents who suffered from at least one chronic disease. We analyzed the distribution characteristics of different indicators among patients using TCM therapies through the χ2 test and determined the main factors influencing the use of TCM therapies through binary logistic regression analysis. Among the 1,023 patients with chronic diseases, 502 (49.07%) used TCM therapies. The five types of TCM therapies were used in the following order of frequency: Chinese herbal medicine (73.11%), cupping (37.45%), acupressure or massage (31.27%), acupuncture (30.48%), and moxibustion (23.11%). Age, self-rated health status, frequency of drinking, frequency of medical visits in the past year, media information sources, types of chronic diseases, and comorbidities significantly affected the use of TCM therapies (P < 0.05). Compared with the population aged over 81 years, patients aged 41–60 years (OR: 1.978, 95% CI: 1.069–3.663) had a higher rate of TCM therapy use. Compared with patients who never drank, those who drank several times a year or less (OR: 1.628, 95% CI: 1.031–2.569) had a higher rate of TCM therapy use. Compared with patients who had never visited a doctor in the past year, those who had visited a doctor several times a week (OR: 2.888, 95% CI: 1.047–7.966), approximately once a week (OR: 3.101, 95% CI: 1.369–7.023), approximately once a month (OR: 1.988, 95% CI: 1.239–3.190), or several times a year (OR: 1.734, 95% CI: 1.202–2.502) had a greater rate of TCM therapy use. Compared with patients whose self-rated health status was poor, those whose self-rated health status was normal (OR: 0.709, 95% CI: 0.504–0.996) had a lower rate of TCM therapy use. Compared with patients who obtained media information through more than three sources, those who obtained it only through television (OR: 0.624, 95% CI: 0.410–0.948) had a lower rate of TCM therapy use. Compared with patients who suffered from three or more chronic diseases simultaneously, those who suffered from hypertension (OR: 0.260, 95% CI: 0.134 ~ 0.507) alone, diabetes (OR: 0.359, 95% CI: 0.149 ~ 0.864) alone, musculoskeletal diseases (OR: 0.466, 95% CI: 0.237 ~ 0.917) alone, other types of chronic diseases (OR: 0.367, 95% CI: 0.191 ~ 0.706) alone, and two (OR: 0.394, 95% CI: 0.212 ~ 0.732) or three (OR: 0.375, 95% CI: 0.186 ~ 0.755) kinds of chronic diseases simultaneously had a lower rate of TCM therapy use. Many factors affect the use of TCM therapies in patients with chronic diseases. The government and relevant departments should understand the trend in the use of TCM therapies in chronic disease management, accurately identify the characteristics of the population that has chronic diseases, optimize publicity channels, enhance the accessibility and acceptance of TCM therapies in global chronic disease health management, and provide practical references for enriching the methods available for preventing and treating chronic diseases.